Comparative Analysis of Concrete Strength Made from Selected Brands of Cement in Anambra State, Nigeria - C. B. N. Bert-Okonkwor; K. C. Okolie; F. O. Ezeokoli; G. C. Ohazulume (Archives of Current Research International, 2020)
The strength characteristics of concrete made from different brands of cement used in Anambra State, Nigeria are reported in this paper. Samples of the selected brands of cement were collected and are used in mixing concrete. The study was conducted in Anambra State, Nigeria for 10 months. Samples of the selected brands of cement were collected and are used in mixing concrete. The fine aggregates used was obtained from River Sand (Onitsha), coarse aggregate is 12 mm quarried granite and water used for the concrete mixing is fit for drinking. These samples of concrete are tested in the laboratory (Anambra State Material Testing Laboratory) for workability and compressive strength and the result obtained were presented in simple tables The study found out that the compressive strength (28th day) of BUA, SUPASET, DANGOTE and UNICEM cements were 30.5, 31.70, 29.66 and 29.08 N/mm2, respectively. Also, the result of the slump value ranges from 70–140 (indicating that the concrete mix is workable) for all the four samples. The results indicate that SUPASET yielded the highest compressive strength (28th day) while UNICEM yielded the lowest compressive strength (28th day). The study was concluded by recommending that all the selected brands of cement within the study area met with the required standard. All concrete samples achieved the minimum compressive strength of concrete (i.e., 21 N/mm2) within 7 days of production. Though the popular cement in the study area is DANGOTE, SUPASET cement is the best cement in terms of strength characteristics while UNICEM possesses the least compressive strength.